Snow - Shulevitz, Uri, 1935- (New York : Farrar Straus Giroux, 2004)
As snowflakes slowly come down, one by one, people in the city ignore them, and only a boy and his dog think that the snowfall will amount to anything.
"A Sunburst book."
Wilson's Children
Elem. School Library Collection
School Library Journal starred
1.5
K-3
Keywords: Snow -- Fiction; City and town life -- Fiction; Snow -- Fiction; City and town life -- Fiction